Polyester release film and method for producing same
The polyester release film with a water-based coating and conductive polymer antistatic layer addresses the issues of non-uniformity and static electricity on silicone-based films, ensuring excellent peelability and coating processability while maintaining low electrostatic voltage.
Patent Information
- Application Number
- JP2024537128
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-12-30
- Filing Date
- 2022-12-23
- Publication Date
- 2024-12-19
- Estimated Expiration
- 2042-12-23
AI Technical Summary
The challenge of forming a uniform barrier coating layer on silicone-based release films is exacerbated by low surface energy and static electricity issues, leading to non-uniform thickness and contamination from static charges.
A polyester release film with a release layer containing a water-based coating composition of polyester resin, acrylic resin, and polyolefin wax, and an antistatic layer with a water-dispersible composition of conductive polymer, which is produced through a method involving stretching and heat-treatment of a laminate.
The film achieves excellent peelability, coating processability, and antistatic properties, reducing static electricity-induced contamination and improving yield by maintaining a frictional electrostatic voltage below 50V.
Smart Images

Figure 2024546293000001 
Figure 2024546293000002 
Figure 2024546293000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a polyester release film and a method for producing the same. [Background technology]
[0002] 2. Description of the Related Art Due to the trend towards larger and thinner displays, there is an increasing demand for thinner polarizing plates in image display devices.
[0003] One method for making a polarizing plate thinner is to make a typical polarizer protective material, such as polyethylene terephthalate (PET), triacetyl cellulose (TAC), etc., thinner. Another method for making a polarizing plate thinner is to replace the polarizer protective material with a coating layer having a barrier property (hereinafter, referred to as a "barrier coating layer").
[0004] The barrier coating layer is formed by uniformly applying the composition for forming the barrier coating layer onto a substrate, curing the composition, and then peeling the composition off.
[0005] To obtain a good quality barrier coating layer, the barrier coating layer must be uniformly applied on the substrate, and the cured barrier coating layer must be easily peeled off from the substrate.
[0006] When a silicone-based release film is used as the substrate, the barrier coating layer is difficult to form with a uniform thickness because the silicone-based release film has low surface energy, and static electricity caused by silicone may occur. Summary of the Invention [Problem to be solved by the invention]
[0007] An object of the present invention is to provide a polyester release film which is excellent in releasability, coating processability and antistatic properties, and which has a low frictional electrostatic voltage.
[0008] Another object of the present invention is to provide a polyester release film that can prevent static electricity from being generated during film running and winding and significantly reduce the amount of air or foreign matter that is introduced due to static electricity.
[0009] It is still another object of the present invention to provide a method for producing the polyester release film. [Means for solving the problem]
[0010] According to one embodiment of the present invention, there is provided a polyester release film comprising a polyester substrate film, a release layer formed on one side of the substrate film, and an antistatic layer formed on the other side of the substrate film, wherein the release layer comprises a water-based coating composition including a polyester resin, an acrylic resin, and a polyolefin wax, and the antistatic layer comprises a water-dispersible antistatic composition including a conductive polymer.
[0011] According to another embodiment of the present invention, there is provided a method for producing a polyester release film, comprising: a first step of preparing a polyester base film; a second step of applying an aqueous coating composition containing a polyester resin, an acrylic resin, and a polyolefin wax to one side of the base film to form a release layer; a third step of applying a water-dispersible antistatic composition containing a conductive polymer to the other side of the base film to form an antistatic layer; and a fourth step of heat-treating a laminate including the base film, the release layer formed on the base film, and the antistatic layer, while stretching the laminate. Effect of the Invention
[0012] The polyester release film according to one embodiment of the present invention has excellent peelability and coating processability, as well as excellent antistatic properties and a remarkably low frictional electrostatic voltage of less than 50V.
[0013] In addition, the polyester release film according to one embodiment of the present invention can prevent static electricity from being generated during film running and winding, and can significantly reduce the amount of air or foreign matter that is introduced due to static electricity.
[0014] The polyester release film according to one embodiment of the present invention can solve problems such as a decrease in yield due to unreacted materials generated when forming a coating layer using the polyester release film, and adhesion of foreign matter due to static electricity. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] The present invention will be described in detail below.
[0016] However, the present invention may be modified in many different forms and should not be construed as limited to the embodiments set forth herein.
[0017] Furthermore, the embodiments of the present invention are provided in order to more completely explain the present invention to those having average knowledge in the art.
[0018] Additionally, as used in the specification and the appended claims, the singular forms "a," "an," and "the" can be intended to include the plural forms as well, unless the context clearly indicates otherwise.
[0019] Furthermore, throughout the specification, "comprising" an element means that it may further include other elements, but not excluding other elements, unless specifically stated to the contrary.
[0020] A polyester release film according to one embodiment of the present invention includes a polyester base film, a release layer formed on one side of the base film, and an antistatic layer formed on the other side of the base film.
[0021] In one embodiment, the release layer may comprise a water-based coating composition including a polyester resin, an acrylic resin, and a polyolefin wax.
[0022] In one embodiment, the antistatic layer may include a water-dispersible antistatic composition including a conductive polymer.
[0023] In one embodiment, the polyester release film may have a frictional electrostatic voltage of less than 50V.
[0024] The present inventors have continuously conducted research into release films that are used as substrates in the production of optical films such as thin film polarizing plates.
[0025] As a result, it was found that when a water-based coating composition containing a polyester resin, an acrylic resin, and a polyolefin wax is applied to a substrate film by an in-line coating method to form a release layer, and a water-dispersible antistatic composition containing a conductive polymer is applied to the other side of the substrate film on which the release layer is not formed to form an antistatic layer, a polyester release film can be provided that is excellent in coating processability and peelability as well as in antistatic properties and low frictional electrostatic voltage, and thus the present invention has been completed.
[0026] The polyester release film not only exhibits excellent coating processability and peelability in post-processing (e.g., a process of forming a barrier coating layer on the release film) after use, but also has a low frictional electrostatic voltage of less than 50 V, thereby preventing contamination due to static electricity.
[0027] The polyester release film includes a polyester base film, a release layer formed on one side of the base film, and an antistatic layer formed on the side of the base film on which the release layer is not formed (hereinafter, the other side).
[0028] The polyester substrate film is made of a polyester resin, and any polyester substrate film commonly used in the technical field to which the present invention pertains can be used without any particular limitation. For example, the polyester substrate film may be made of polyethylene terephthalate, polyethylene naphthalate, etc.
[0029] As a non-limiting example, the base film may be advantageously made of polyethylene terephthalate having an intrinsic viscosity in the range of 0.6 to 0.8 dl / g in terms of ensuring resistance to oxidation and hydrolysis.
[0030] The release layer may comprise a water-based coating composition including a polyester resin, an acrylic resin, and a polyolefin wax.
[0031] The polyester resin is a resin obtained by polycondensation of an acid component mainly composed of a dicarboxylic acid and a glycol component mainly composed of an alkylene glycol. As the acid component, terephthalic acid or its alkyl ester or phenyl ester can be mainly used, and a part of it can be replaced with isophthalic acid, oxyethoxybenzoic acid, adipic acid, sebacic acid, 5-sodium sulfoisophthalic acid, sulfoterephthalic acid, etc. As the glycol component, ethylene glycol, diethylene glycol, etc. can be mainly used, and a part of it can be replaced with propylene glycol, trimethylene glycol, 1,4-cyclohexanediol, 1,4-cyclohexanedimethanol, 1,4-bisoxyethoxybenzene, bisphenol, polyoxyethylene glycol, etc.
[0032] As a non-limiting example, the polyester resin can be obtained by polycondensation of 50 mol % of a glycol component containing diethylene glycol and ethylene glycol in a molar ratio of 5:5, and 50 mol % of an acid component containing terephthalic acid and sulfoterephthalic acid in a molar ratio of 8.5:1.5.
[0033] The polyester resin may have a weight average molecular weight of 2,000 to 25,000 g / mol, which is advantageous for providing the release layer with suitable solvent resistance. Preferably, the weight average molecular weight of the polyester resin may be 2,000 to 25,000 g / mol, or 2,000 to 20,000 g / mol, or 3,000 to 20,000 g / mol, or 3,000 to 15,000 g / mol.
[0034] In the present specification, the weight average molecular weight means a weight average molecular weight in terms of polystyrene measured by a GPC method. In the process of measuring the weight average molecular weight in terms of polystyrene measured by the GPC method, a commonly known analyzer, a detector such as a refractive index detector, and an analytical column may be used, and commonly used temperature conditions, solvents, and flow rates may be applied.
[0035] The acrylic resin may contain a glycidyl group-containing radical polymerizable unsaturated monomer as a copolymerization monomer in an amount of 20 to 80 mol % of the total monomer components. The glycidyl group-containing radical polymerizable unsaturated monomer is preferred because it can improve the strength of the release layer by a crosslinking reaction and prevent the outflow of oligomers. Examples of the glycidyl group-containing radical polymerizable unsaturated monomer include glycidyl acrylate, glycidyl methacrylate, and aryl glycidyl ether.
[0036] Examples of the radically polymerizable unsaturated monomer that can be copolymerized with the glycidyl group-containing radically polymerizable unsaturated monomer include vinyl esters, unsaturated carboxylic acid esters, unsaturated carboxylic acid amides, unsaturated nitriles, unsaturated carboxylic acids, allyl compounds, nitrogen-containing vinyl monomers, hydrocarbon vinyl monomers, and vinyl silane compounds. Examples of the vinyl esters include vinyl propionate, vinyl stearate, and vinyl chloride. Examples of the unsaturated carboxylic acid esters include methyl acrylate, ethyl acrylate, butyl acrylate, 2-ethylhexyl acrylate, ethyl methacrylate, butyl methacrylate, butyl maleate, octyl maleate, butyl fumarate, octyl fumarate, hydroxyethyl methacrylate, hydroxyethyl acrylate, hydroxypropyl methacrylate, and hydroxypropyl acrylate. Examples of the unsaturated carboxylic acid amides include acrylamide, methacrylamide, methylol acrylamide, and butoxymethylol acrylamide. Examples of the unsaturated nitriles include acrylonitrile. Examples of the unsaturated carboxylic acid include acrylic acid, methacrylic acid, maleic acid, fumaric acid, itaconic acid, maleic acid ester, fumaric acid ester, and itaconic acid ester. Examples of the allyl compound include allyl acetate, allyl methacrylate, allyl acrylate, allyl itaconate, and diallyl itaconate. Examples of the nitrogen-containing vinyl monomer include vinylpyridine and vinylimidazole. Examples of the hydrocarbon vinyl monomer include ethylene, propylene, hexene, octene, styrene, vinyltoluene, and butadiene. Examples of the vinylsilane compound include dimethylvinylmethoxysilane, dimethylvinylethoxysilane, methylvinyldimethoxysilane, methylvinyldiethoxysilane, γ-methacryloxypropyltrimethoxysilane, and γ-methacryloxypropyldimethoxysilane.
[0037] As a non-limiting example, the acrylic resin may be a copolymer of 40 to 60 mol % of glycidyl acrylate and 40 to 60 mol % of propionic acid.
[0038] The acrylic resin preferably has a weight average molecular weight of 20,000 to 70,000 g / mol. More preferably, the weight average molecular weight of the polyester resin may be 20,000 to 60,000 g / mol, 30,000 to 60,000 g / mol, 40,000 to 60,000 g / mol, or 45,000 to 55,000 g / mol.
[0039] In one embodiment, the weight ratio of the solid content of the polyester resin to the acrylic resin may be 1:0.1 to 1:1.5, more specifically, 1:0.2 to 1:1. When a release layer is produced from an aqueous coating composition satisfying this range, the polyester release film may have an effect of not only excellent releasability but also further improving process coating properties.
[0040] The release layer may contain a polyolefin wax, and may be in a form dispersed on the polyester resin and the acrylic resin.
[0041] The specific type of the polyolefin wax is not particularly limited, but one or more types selected from the group consisting of polyethylene wax and polypropylene wax can be preferably used.
[0042] The polyolefin wax may be included in an amount of 20 to 50 parts by weight or 30 to 40 parts by weight based on 100 parts by weight of the polyester resin. In order for the release layer to exhibit an appropriate peel strength, the polyolefin wax is preferably included in an amount of 20 parts by weight or more based on 100 parts by weight of the polyester resin. However, if an excessive amount of the polyolefin wax is added to the release layer, a back transfer problem and a decrease in process coating properties may be induced. Therefore, the polyolefin wax is preferably included in an amount of 50 parts by weight or less based on 100 parts by weight of the polyester resin.
[0043] For example, the polyolefin wax may be included in an amount of 20 parts by weight or more, or 25 parts by weight or more, or 30 parts by weight or more, and 50 parts by weight or less, or 45 parts by weight or less, or 40 parts by weight or less, based on 100 parts by weight of the polyester resin. Specifically, the polyolefin wax may be included in an amount of 20 to 50 parts by weight, or 25 to 50 parts by weight, or 25 to 45 parts by weight, or 30 to 45 parts by weight, or 30 to 40 parts by weight, based on 100 parts by weight of the polyester resin.
[0044] The total content of the polyester resin, the acrylic resin and the polyolefin wax contained in the water-based coating composition is preferably 1 to 10 wt%, 2 to 9 wt%, 4 to 8 wt%, or 5 to 6 wt% based on the solid content.
[0045] The polyester release film manufactured by satisfying the above ranges for the total content based on solid content of the binder and the polyolefin wax contained in the aqueous coating composition not only has excellent transfer properties and peelability, but also has a significantly reduced frictional electrostatic voltage of less than 50 V. In addition, the release film manufactured by satisfying the above ranges can prevent the occurrence of fine pinholes, thereby improving process coating properties.
[0046] In one embodiment of the present invention, the aqueous coating composition applied to the release layer may further contain additives such as silicone-based wetting agents, fluorine-based wetting agents, curing agents, acid catalysts, slip agents, defoamers, wetting agents, surfactants, thickeners, plasticizers, antioxidants, UV absorbers, preservatives, and crosslinking agents, if necessary. The additives may be selectively used within the limits that do not impair the physical properties of the release layer.
[0047] The antistatic layer may include a water-dispersible antistatic composition that includes a conductive polymer.
[0048] The polyester release film according to one embodiment of the present invention includes the release layer and the antistatic layer made of a non-silicone-based material, and therefore has excellent coating processability and peelability, as well as excellent antistatic properties and a remarkably low frictional electrostatic voltage of less than 50V.
[0049] The conductive polymer may be a nano-sized structure having electrical conductivity and polarity. The conductive polymer may include at least one selected from the group consisting of polythiophene-based, polypyrrole-based, and polyaniline-based conductive polymers.
[0050] In one embodiment, the conductive polymer may include a resin composition containing the conductive polymer. The resin may be, for example, a water-based resin or may contain an ionic polymer.
[0051] The ionic polymer is a polymer having a group containing a cationic or anionic group, and may be an ionic polymer such as polystyrene sulfonate, polystyrene ammonium salt, etc., but is not limited thereto. When the ionic polymer is used, the content is not limited as long as the object of the present invention is achieved, and may be used in a weight ratio of 0.01 to 2 with respect to the conductive polymer, for example.
[0052] In one embodiment, the conductive polymer may be a polythiophene-based conductive polymer or may be polyethylenedioxythiophene:polystyrenesulfonate (PEDOT:PSS). When PEDOT:PSS is used as the conductive polymer, it has excellent water dispersibility and is suitable for use in an in-line coating process. Its transparency does not decrease even after a stretching process after the in-line coating process, and it can be used for 10 10 It is more preferred because it can exhibit a surface resistance of Ω / □ or less.
[0053] The water-dispersible antistatic composition may further include a water-based polyurethane resin. By mixing the water-based polyurethane resin with a conductive polymer, an antistatic layer having excellent miscibility, improved surface resistance, excellent adhesion to a polyester base film, little change in physical properties under high temperature and high humidity conditions, and little yellowing can be formed. The water-based polyurethane resin uses a polyurethane binder obtained by reacting a polycarbonate-based polyol with a diisocyanate, and thus can achieve physical properties having excellent heat resistance and a small rate of change in surface resistance. More preferably, hexamethylene diisocyanate is used as a specific example of the diisocyanate from the viewpoint of improving heat resistance and forming a coating film with little yellowing, but is not limited thereto.
[0054] In one embodiment, the water-dispersible antistatic composition may contain 1-30 wt% conductive polymer and 70-99 wt% water-based polyurethane resin in a solid content of 100 wt%. More specifically, the water-dispersible antistatic composition may contain 5-25 wt% conductive polymer and 75-95 wt% polyurethane binder. More specifically, the water-dispersible antistatic composition may contain 5-20 wt% conductive polymer and 80-95 wt% polyurethane binder.
[0055] More specifically, the antistatic layer may be formed by applying a water-dispersible antistatic composition containing a conductive polymer solution, a water-based polyurethane resin solution, an organic solvent, and water.
[0056] More specifically, for example, the water-dispersible antistatic composition may contain 40 to 90 wt % of a conductive polymer solution having a solid content of 1 to 3 wt %, 5 to 50 wt % of a water-based polyurethane resin solution having a solid content of 30 to 40 wt %, 3 to 50 wt % of an organic solvent, and the balance water.
[0057] The conductive polymer may be used as a conductive polymer solution in a state where it is mixed in a solvent to exhibit optimal dispersibility. Specifically, for example, when PEDOT:PSS is used, it may be mixed with water, alcohol, a solvent having a large dielectric constant, etc.
[0058] The content of the conductive polymer solution in the antistatic composition may be 40 to 90 wt %, more preferably 50 to 70 wt %, which is sufficient to achieve the object of the invention, but is not limited thereto.
[0059] In addition, the aqueous polyurethane resin may be dispersed in a solvent. The solvent is not limited, but may be any one or a mixture of two or more selected from the group consisting of amide-based organic solvents and aprotic highly dipolar (AHD) organic solvents.
[0060] The content of the water-based polyurethane resin in the water-dispersible antistatic composition may be 5 to 50 wt %, more preferably 10 to 30 wt %, but is of course not limited thereto.
[0061] The organic solvent is not particularly limited, and may be any one or a mixture of two or more selected from the group consisting of alcohol-based organic solvents and aprotic highly polar organic solvents, but is not limited thereto.
[0062] The content of the organic solvent in the water-dispersible antistatic composition may be 50 wt % or less, 40 wt % or less, 30 wt % or less, 20 wt % or less, or 10 wt % or less, and the lower limit may be 1 wt % or 2 wt % or more, and within the above range, it is a content suitable for improving the dispersibility of the conductive polymer and the water-based polyurethane resin, but is not limited thereto.
[0063] The alcohol-based organic solvent is not limited, and specifically, for example, methanol, ethanol, propanol, isopropanol, butanol, and 2-amino-2-methyl-1-propanol can be used alone or in combination.
[0064] The aprotic highly polar organic solvent is not limited, but specifically, for example, dimethyl sulfoxide, propylene carbonate, etc. may be used alone or in combination of two or more. The use of the aprotic highly polar organic solvent can further improve the conductivity of the conductive polymer.
[0065] Since the water-dispersible antistatic composition contains each material in the above content range, the polyester release film according to one embodiment of the present invention has a significantly low frictional electrostatic voltage of less than 50 V and has excellent antistatic properties, and can prevent static electricity generated during film running and winding, and can significantly reduce the amount of air or foreign matter that is drawn in by static electricity.
[0066] In addition, since the water-dispersible antistatic composition satisfies the above content range, the polyester release film according to one embodiment of the present invention can solve problems such as a decrease in yield due to unreacted materials generated when forming a coating layer using the composition, and adhesion of foreign matter due to static electricity.
[0067] In one embodiment of the present invention, the surface resistance of the antistatic layer is 10 10 It may be Ω / □ or less, more specifically, 10 9 It may be Ω / □ or less.
[0068] In one embodiment of the present invention, the water-dispersible antistatic composition may further include a silicone-based wetting agent, a fluorine-based wetting agent, a slip agent, a defoaming agent, a wetting agent, a surfactant, a thickener, a plasticizer, an antioxidant, an ultraviolet absorbing agent, a preservative, and a crosslinking agent, if necessary.
[0069] The thicknesses of the base film, release layer, and antistatic layer are not particularly limited and can be adjusted according to the specific application field of the polyester release film.
[0070] For example, the base film may have a thickness of 10 to 300 μm, and the release layer and antistatic layer may have a thickness of 10 to 200 nm, but are not necessarily limited thereto.
[0071] The thicknesses of the release layer and the antistatic layer may be the same or different from each other. Specifically, the thickness of the base film may be 10 to 200 μm, 10 to 100 μm, or 10 to 50 μm, the thickness of the release layer may be 10 to 100 nm, more specifically 50 to 100 nm, and the thickness of the antistatic layer may be 10 to 100 nm, more specifically 20 to 80 nm.
[0072] In the polyester release film, the base film may be, but is not limited to, uniaxially stretched in the machine direction (MD) or transverse direction (TD), or biaxially stretched in the machine direction (MD) and transverse direction (TD), and the release layer and antistatic layer may be uniaxially or biaxially stretched, but is preferably uniaxially stretched in the transverse direction (TD) since the properties of the present invention can be better imparted.
[0073] By satisfying the above-mentioned characteristics, the polyester release film may have excellent releasability, as well as low frictional electrostatic voltage, and thus excellent antistatic properties.
[0074] For example, the polyester release film may have a peel strength of 350 to 700 gf / inch, or 400 to 650 gf / inch, or 400 to 600 gf / inch. A polyester release film having a peel strength within the above range may have excellent coating processability and peelability in post-processing (e.g., a process of forming a barrier coating layer on the release film).
[0075] In this specification, the peel strength is measured according to the standard test method of ASTM D 3330. Specifically, the peel strength was measured by laminating an acrylate adhesive tape (NITTO#31B, manufactured by Nitto Denko, tape width: 25 mm) cut to a size of 5 mm x 180 mm on the release layer of the polyester release film, and applying a peel strength of 70 g / cm 2 After applying a load of 100 mm and leaving it at room temperature for 30 minutes, the tape is peeled off at 180 degrees at a peeling speed of 300 mm / min using a peel tester to measure the strength of the tape.
[0076] In addition, the polyester release film may have a significantly low frictional electrostatic voltage of less than 50 V, or less than 40 V, or less than 30 V, or less than 20 V, or less than 10 V. The lower limit of the frictional electrostatic voltage is not particularly limited, but may be, for example, 1 V or more, 3 V or 5 V or more.
[0077] In this specification, the frictional electrostatic voltage is measured according to the standard test method of KS K 0555. Specifically, the frictional electrostatic voltage can be measured by using a conventional rotary static tester to measure the frictional static electricity of the polyester release film. Here, the A side (the release layer side of the polyester release film) and the B side (the antistatic layer side of the polyester release film) are rubbed at a rotation speed of 300 rpm for 180 seconds to measure the amount of static electricity generated.
[0078] Furthermore, the polyester release film can exhibit excellent processing and coating properties while having a low haze value.
[0079] For example, the polyester release film may have a haze of 3.90% or less. Preferably, the polyester release film may have a haze of 3.50 to 3.90%, 3.60 to 3.90%, or 3.70 to 3.86%.
[0080] In addition, the polyester release film can have excellent processing and coating properties that satisfy the following formula 1.
[0081] [Formula 1] N H =0
[0082] In the above formula 1, N H is the unit area (m) when a UV resin is applied to a thickness of 10 μm on the release layer of the polyester release film and cured. 2 ) is the number of pinholes generated per
[0083] That is, when any resin layer is formed on the release layer in any manufacturing process using the polyester release film as a substrate, substantially no pinholes are formed on the release layer, and excellent processing and coating properties can be exhibited.
[0084] In addition, the polyester release film can exhibit a total light transmittance of 90% to 95%, a water contact angle of 85° to 90°, a diiodomethane contact angle of 50° to 60°, and a surface energy of 30 to 35 mN / m.
[0085] In addition, the polyester release film according to one embodiment of the present invention may be a polyester release film for thin film polarizers, but is not limited thereto and can be applied to various fields requiring antistatic properties, coating processability, and releasability. For example, in addition to thin film polarizer applications, the polyester release film can be used as a cover tape for MLCC (Multi Layer Ceramic Capacitor) carriers, for FPCB (Flexible Printed Circuits Board) process protection, for OCA (Optically Clear Adhesive) and OCA protection, and for protecting the surfaces of optical members for displays (various display surfaces).
[0086] In the polyester release film, the release layer and the antistatic layer may be formed on the polyester substrate film by in-line coating. The release layer may be formed by applying a water-based coating composition containing the polyester resin, an acrylic resin, and a polyolefin wax to one side of the polyester substrate film by an in-line coating method.
[0087] The antistatic layer may be formed by applying a water-dispersible antistatic composition including the conductive polymer to the other surface of the substrate film by an in-line coating method.
[0088] The release layer and the antistatic layer are formed by an in-line coating method, and therefore, although the coating thickness is thin, they have excellent adhesion to the polyester substrate film and exhibit excellent resistance to moisture and solvents.
[0089] The polyester release film has excellent coating processability, peelability, and low frictional charging voltage, and can be suitably used as a release substrate film when manufacturing a thin film polarizing plate.
[0090] As a non-limiting example, when manufacturing the thin film polarizer, a laminate may be formed by sequentially laminating a barrier coating layer; a polyvinyl alcohol resin layer; an adhesive layer; and a resin layer such as polyethylene terephthalate (PET), triacetyl cellulose (TAC), or polymethyl methacrylate (PMMA) on the substrate film of the polyester release film.
[0091] Additionally, the polyester release film can be removed from the laminate.
[0092] The method for producing the polyester release film will be described in detail below.
[0093] A method for producing a polyester release film according to one embodiment of the present invention may include a first step of preparing a polyester base film; a second step of applying an aqueous coating composition including a polyester resin, an acrylic resin, and a polyolefin wax to one side of the base film to form a release layer; a third step of applying a water-dispersible antistatic composition including a conductive polymer to the other side of the base film to form an antistatic layer; and a fourth step of stretching and heat-treating a laminate including the base film and the release layer and antistatic layer formed on the base film.
[0094] The first step is to prepare a polyester base film, which is made of a polyester resin.
[0095] As the polyester substrate film, any film commonly used in the technical field to which the present invention belongs can be used without any particular limitation. The polyester substrate film can be prepared as one stretched in the machine direction (MD, or length direction), although it is not necessarily limited thereto. Preferably, the polyester substrate film may be stretched 2 to 5 times in the machine direction (MD). The polyester substrate film preferably has a thickness of 10 to 300 μm, but is of course not limited thereto within the limits for achieving the object of the present invention.
[0096] The second step is a step of forming a release layer by applying an aqueous coating composition containing a polyester resin, an acrylic resin, and a polyolefin wax to one side of the base film, and the aqueous coating composition is for forming the release layer on the polyester base film.
[0097] The water-based coating composition may contain the polyester resin, the acrylic resin, and the polyolefin wax, and the specific details regarding the resin and the wax may be as described above.
[0098] The aqueous coating composition may be prepared by uniformly mixing the above-mentioned components with water. The solid content of the aqueous coating composition may be preferably 20 to 60 wt% in order to ensure the efficiency of the coating process.
[0099] The release layer may be formed on one side of the polyester substrate film by an in-line coating method using the aqueous coating composition. By forming the release layer by the in-line coating method, the coating thickness is thin, but the release layer has excellent adhesion to the polyester substrate film and exhibits excellent resistance to moisture and solvents.
[0100] The in-line coating method can be carried out using conventional equipment.
[0101] In the in-line coating, the aqueous coating composition can be applied so that the thickness of the release layer is 20 to 200 nm after the final stretching and drying. The specific details regarding the thickness and other properties of the release layer can be as described above.
[0102] The release layer can be formed by applying the aqueous coating composition onto the polyester substrate film, and then removing water from the aqueous coating composition and curing the composition.
[0103] The third step is a step of forming an antistatic layer by applying a water-dispersible antistatic composition including a conductive polymer to the other surface of the substrate film. The water-dispersible antistatic composition may further include a water-based polyurethane resin. The specific details regarding the conductive polymer, the water-based polyurethane resin, etc. may be as described above.
[0104] The water-dispersible antistatic composition may be prepared by uniformly mixing the above-mentioned components with water. The solid content of the antistatic composition may be preferably 5 to 50 wt % in order to ensure the efficiency of the coating process.
[0105] The water-dispersible antistatic composition may further include an organic solvent, and the details thereof may be as described above.
[0106] The antistatic layer may be formed on the other side of the polyester substrate film by an in-line coating method using the water-dispersible antistatic composition, and the details of the in-line coating method may be the same as those described above for the release layer.
[0107] The fourth step is a step of heat-treating the laminate including the base film and the release layer and antistatic layer formed on the base film while stretching it in the machine direction (MD) or the transverse direction (TD).
[0108] In one embodiment, although not necessarily limited thereto, when the laminate is stretched 2 to 5 times in the transverse direction (TD), this is preferred since this embodiment of the present invention is suitable for achieving the desired physical properties.
[0109] For example, the release layer and the antistatic layer can be formed on the polyester substrate film uniaxially stretched in the machine direction (MD), and then stretched in the transverse direction (TD). Through this stretching process, the polyester substrate film is biaxially stretched in the machine direction and the transverse direction, and the release layer and the antistatic layer are uniaxially stretched in the transverse direction.
[0110] The fourth step can be carried out using a conventional heat treatment device such as a tenter. In the fourth step, the laminate can be continuously passed through the tenter.
[0111] The laminate is preheated while passing through a front stage of the tenter, stretched, for example, in a transverse direction (TD) while passing through a middle stage of the tenter, and heat-treated while passing through a rear stage of the tenter. The heat treatment may be performed by heating the laminate while maintaining the tension applied to the laminate during the transverse stretching.
[0112] Preferably, the fourth step can be performed by passing the laminate through a heat treatment device in which the total heat amount of air supplied to the passage section is 222,000 kcal / min to 229,000 kcal / min. The laminate passing through the heat treatment device is stretched and heat-treated while being exposed to the total heat amount range.
[0113] Specifically, the fourth step can be performed by passing the laminate through a heat treatment device in which the total calorific value of air supplied to the entire passage section is 222,000 kcal / min to 229,000 kcal / min, alternatively 225,000 kcal / min to 229,000 kcal / min, alternatively 226,000 kcal / min to 229,000 kcal / min, alternatively 226,000 kcal / min to 228,000 kcal / min, or alternatively 226,000 kcal / min to 227,000 kcal / min.
[0114] In the fourth step, the total calorific value (kcal) of the air supplied to the entire section through which the laminate passes can be calculated from data such as the temperature (°C) of the section, the mass (kg / min) of the air supplied to the heat treatment device, and the specific heat of the air (kcal / kg°C). The mass (kg / min) of the air is calculated based on the volumetric flow rate (Nm 3 / min) and air density (kg / Nm 3 ) can be obtained.
[0115] For example, in the heat treatment device, the density of air supplied to a given zone is 1.286 kg / Nm 3 The specific heat of air is 0.24 kcal / kg℃, and the volumetric flow rate of air is 380 Nm 3 / min, the initial temperature of the air is 20°C, and the set temperature of the section is 220°C, the total calorific value (kcal) of the air supplied to the section can be calculated as 23,456.64 kcal / min using the following calculation formulas 1 and 2.
[0116] [Formula 1] Mass of air (kg / min) = Volumetric flow rate of air (Nm 3 / min) × air density (kg / Nm 3 )
[0117] [Formula 2] Heat content of air (kcal / min) = mass of air (kg / min) x specific heat of air (kcal / kg℃) x temperature change (℃)
[0118] When the passage length of the section is 3 m and the laminate passes through the section at a speed of 100 m / min, the amount of heat exposed to the laminate in the section can be calculated as 7,037 kcal / zone according to Equation 3 below.
[0119] [Formula 3] Amount of heat exposed to the laminate (kcal / zone) = Amount of heat in the air (kcal / min) × Passage length of the section (m / zone) × Speed of the laminate (m / min)
[0120] According to one embodiment of the invention, the method can include the steps of preheating the laminate by passing it through a section where a heat amount of 44,000 kcal / min to 46,000 kcal / min is supplied; stretching the preheated laminate in the machine direction (MD) or transverse direction (TD) while passing it through a section where a heat amount of 62,000 kcal / min to 64,000 kcal / min is supplied; and heat treating the stretched laminate while passing it through a section where a heat amount of 114,000 kcal / min to 120,000 kcal / min is supplied.
[0121] Preferably, the preheating step can be carried out while passing the laminate through a section to which a heat quantity of 45,000 kcal / min to 46,000 kcal / min is supplied.
[0122] Preferably, the stretching step can be performed while passing the preheated laminate through a section to which a heat quantity of 63,000 kcal / min to 64,000 kcal / min is supplied.
[0123] Preferably, the heat treatment step can be carried out while passing the stretched laminate through a section to which a heat amount of 115,000 kcal / min to 120,000 kcal / min, alternatively 115,000 kcal / min to 119,000 kcal / min, alternatively 116,000 kcal / min to 119,000 kcal / min, alternatively 117,000 kcal / min to 118,500 kcal / min, or alternatively 118,000 kcal / min to 118,500 kcal / min is supplied.
[0124] If the total heat amount of the air supplied to the passage section in the fourth stage (particularly, the heat treatment zone after stretching) is too low, the releasability and transferability of the polyester release film may deteriorate and the frictional charging voltage may increase. If the total heat amount of the air supplied to the passage section in the fourth stage (particularly, the heat treatment zone after transverse stretching) is too high, the surface energy of the polyester release film may decrease, and the processing and coating properties may decrease.
[0125] In the fourth stage, the laminate preferably passes through the heat treatment device at a speed of 80 m / min to 120 m / min, or 90 m / min to 110 m / min, or 90 m / min to 100 m / min.
[0126] In carrying out the fourth step, it is preferable that the laminate passes through the heat treatment device within the speed range so that the laminate is exposed to an appropriate amount of heat in each section and the transverse stretching and heat treatment are sufficiently performed.
[0127] The fourth step can be carried out at a temperature of 120° C. to 245° C. For example, the fourth step can be carried out by the steps of preheating the laminate at a temperature of 120° C. to 150° C., stretching the preheated laminate in the transverse direction at a temperature of 130° C. to 150° C., and heat-treating the stretched laminate at a temperature of 215° C. to 245° C.
[0128] In particular, the step of heat-treating the stretched laminate can be performed at 215° C. or more, 220° C. or more, 225° C. or more, or 230° C. or more; and 245° C. or less, or 240° C. or less. Specifically, the step of heat-treating the stretched laminate can be performed at 215-245° C., 220-245° C., 220-240° C., 225-240° C., or 230-240° C.
[0129] When the temperature of the heat treatment process of the stretched laminate satisfies the above range, not only the releasability of the polyester release film is excellent, but also the frictional charging voltage is reduced, and fine pinholes are not generated during the production of the polyester release film, and processing and coating properties can be improved.
[0130] After the fourth step, a process of relaxing the film by 2 to 10% in both the machine direction and the transverse direction at 150° C. to 200° C. may be carried out.
[0131] The polyester release film obtained through the above process may have a final thickness of 20 to 100 μm, or 30 to 80 μm, or 30 to 50 μm.
[0132] The present invention will be specifically illustrated and described below with Production Examples, Examples, and Experimental Examples. However, the Examples and Experimental Examples described later are merely illustrative of a part of the present invention, and the present invention is not limited thereto. EXAMPLES
[0133] <Preparation Example 1> Preparation of the first aqueous coating composition (1) Preparation of the first resin composition A 50 mol % glycol component containing diethylene glycol and ethylene glycol in a molar ratio of 5:5, and a 50 mol % acid component containing terephthalic acid and sulfoterephthalic acid in a molar ratio of 8.5:1.5 were subjected to condensation polymerization to obtain a first polyester resin (weight average molecular weight 10,000 g / mol).
[0134] 100 parts by weight of the first polyester resin and 25 parts by weight of polyethylene wax (Wax No. 1, Takamatsu Co., Ltd., Japan) were added to distilled water and stirred for 30 minutes to prepare a first resin composition (solid content 20 wt%).
[0135] (2) Preparation of the second resin composition A second polyester resin (weight average molecular weight 3,000 g / mol) was obtained by condensation polymerization of 50 mol% of a glycol component containing diethylene glycol and ethylene glycol in a molar ratio of 5:5, and 50 mol% of an acid component containing terephthalic acid and sulfoterephthalic acid in a molar ratio of 8.5:1.5.
[0136] An acrylic resin was obtained by copolymerizing 60 mol % of glycidyl acrylate and 40 mol % of vinyl propionate (weight average molecular weight: 50,000 g / mol).
[0137] 50 parts by weight of the second polyester resin, 50 parts by weight of the acrylic resin, and 25 parts by weight of polyethylene wax were added to distilled water and stirred for 30 minutes to prepare a second resin composition (solid content 20 wt %).
[0138] (3) Preparation of Water-Based Coating Composition A first aqueous coating composition was prepared by mixing 14.3 wt % (solid content 20 wt %) of the first resin composition, 14.3 wt % (solid content 20 wt %) of the second resin composition, 0.2 wt % of a silicone-based wetting agent (Dow Corning, Q2-5212, solid content 90 wt %), 0.2 wt % of a fluorine-based wetting agent (DuPont, FS-31, solid content 25 wt %), and the remaining amount of water.
[0139] <Preparation Example 2> Preparation of second aqueous coating composition A second aqueous coating composition was prepared in the same manner as in Preparation Example 1, except that the first resin composition prepared in Preparation Example 1 was not used and the second resin composition was further used in the same amount. That is, the second aqueous coating composition according to Preparation Example 2 contained 28.6 wt% of the second resin composition.
[0140] <Preparation Example 3> Preparation of the first antistatic coating composition 60wt% of conductive polymer aqueous dispersion (Heraeus, Clevios P, solid content 1.3wt%), 6wt% of water, and 5wt% of isopropyl alcohol (IPA) are added to a mixing vessel and stirred for 1 hour, 2wt% of 2-amino-2-methyl-1-propanol (Alfa aesar, 95%) is added to the mixing vessel and stirred again for 1 hour, 20wt% of water-based polyurethane resin (Neo resins, NeorezR-960, solid content 31wt%) is added and stirred again for 30 minutes, and 5wt% of dimethyl sulfoxide and 2wt% of silicone-based wetting agent (BYK 348) are added to the mixing vessel and stirred for 1 hour to prepare a first water-dispersible antistatic composition (solid content 6.98wt%). Then, the first water-dispersible antistatic composition is diluted a second time to prepare the first water-dispersible antistatic composition. In this case, 30 wt % of the first water-dispersible antistatic composition, 69.6 wt % of water, 0.2 wt % of a silicone-based wetting agent (Dow Corning, Q2-5212, solid content 90 wt %), and 0.2 wt % of a fluorine-based wetting agent (DuPont, FS-31, solid content 25 wt %) were mixed to prepare a first antistatic coating composition.
[0141] Comparative Preparation Example 1 Preparation of the third aqueous coating composition A third aqueous coating composition was prepared by mixing 20 wt% silicone release base (Wacker, 400E, solids 55 wt%), 1.1 wt% hardener (Wacker, V-72, solids 40 wt%), 0.18 wt% silicone wetting agent (DowCorning, Q2-5212, solids 90 wt%), 5 wt% isopropyl alcohol (IPA), and the remaining amount of water.
[0142] Comparative Preparation Example 2 Preparation of the fourth aqueous coating composition A fourth aqueous coating composition was prepared in the same manner as in Preparation Example 1, except that the second resin composition prepared in Preparation Example 1 was not used and the first resin composition was further used in the same amount. That is, the fourth aqueous coating composition according to Comparative Preparation Example 1 contained only 28.6 wt% of the first resin composition.
[0143] Comparative Preparation Example 3: Preparation of second antistatic coating composition A second antistatic coating composition was prepared by mixing 5.1 wt% of an acrylic water dispersion (ATX-014, Takamatsu Corporation, solid content 40 wt%), 9 wt% of an anionic polymer antistatic agent (JINBO Co., Ltd., ICP-323, molecular weight 100,000 g / mol or more, solid content 25.5 wt%), 2 wt% of a silicone wetting agent (BYK 384), and the remaining amount of water.
[0144] <Example 1> (1) PET chips with moisture content of 100 ppm or less were injected into a melt extruder and melted, then extruded through a T-die and rapidly cooled and solidified on a casting drum with a surface temperature of 20° C. to produce a PET sheet. The produced PET sheet was stretched 3.5 times in the machine direction at 110° C. and cooled to room temperature to obtain the PET substrate film.
[0145] (2) Using a gravure coater, the first aqueous coating composition according to Preparation Example 1 was applied to one side of the PET substrate film to a thickness of 70 nm after final drying to form a release layer, and the first antistatic coating composition according to Preparation Example 3 was applied to the other side of the PET substrate film to a thickness of 50 nm after final drying to form an antistatic layer.
[0146] (3) Next, the laminate having the release layer and the antistatic layer formed thereon was heat-treated while being stretched 4 times in the transverse direction (TD) in a tenter divided into a preheating zone, a stretching zone, and a heat treatment zone.
[0147] The heat treatment step was performed while the laminate (initial width: 5.12 m, initial thickness: 152 μm) was passed through the tenter having a total length of 33 m and including a preheating zone, a stretching zone, and a heat treatment zone in that order at a moving speed of 100 m / min.
[0148] The heat treatment step was performed while passing the laminate through the tenter in which the total heat amount of air supplied to the passage section was 226,400 kcal / min.
[0149] The density of the air supplied to the tenter is 1.286 kg / nm 3 The specific heat of air was confirmed to be 0.24 kcal / kg℃, and the volumetric flow rate of air was 270-680 nm. 3 / min range.
[0150] Specifically, the laminate passed through the preheating zone (7.5 m long) where a heat amount of 45,000 kcal / min was supplied at a temperature of about 120°C to 130°C. Then, the preheated laminate was stretched 4 times in the transverse direction while passing through the stretching zone (10.5 m long) where a heat amount of 63,200 kcal / min was supplied at a temperature of about 130°C to 140°C. Then, the stretched laminate was heat-treated while passing through the heat treatment zone (15 m long) where a heat amount of 118,200 kcal / min was supplied at a temperature of 230°C to 235°C.
[0151] (4) After the heat treatment, the film was heat-set at 200° C. while being relaxed by 10% in each of the machine direction and the transverse direction to prepare a polyester release film having a total thickness of 38 μm.
[0152] <Example 2> In Example 2, a polyester release film having a total thickness of 38 μm was prepared in the same manner as in Example 1, except that the release layer of Example 1 was formed by coating the second aqueous coating composition of Preparation Example 2.
[0153] <Comparative Example 1> In Comparative Example 1, a polyester release film having a total thickness of 38 μm was prepared in the same manner as in Example 1, except that the antistatic layer was not formed.
[0154] <Comparative Example 2> In Comparative Example 2, a polyester release film having a total thickness of 38 μm was prepared in the same manner as in Example 1, except that the release layer of Example 1 was formed by coating the third aqueous coating composition of Comparative Preparation Example 1.
[0155] <Comparative Example 3> In Comparative Example 3, a polyester release film having a total thickness of 38 μm was manufactured in the same manner as in Comparative Example 2, except that the antistatic layer was not formed.
[0156] <Comparative Example 4> In Comparative Example 4, a polyester release film having a total thickness of 38 μm was prepared in the same manner as in Example 1, except that the second antistatic coating composition of Comparative Preparation Example 3 was used as the antistatic layer of Example 1.
[0157] <Comparative Example 5> In Comparative Example 5, a polyester release film having a total thickness of 38 μm was prepared in the same manner as in Example 1, except that the release layer of Example 1 was formed by coating the fourth aqueous coating composition of Comparative Preparation Example 2.
[0158] <Evaluation items> The following properties of the examples and comparative examples were measured and the measured values are shown in Table 1 below.
[0159] 1.Optical properties The haze and total light transmittance (TT) of the films of the following Examples and Comparative Examples were measured using a Haze Meter (Nippon Denshoku, NDH 5000).
[0160] 2. Transfer test An untreated PET base film was laminated onto the release layer of a polyester release film, and a load of 50 gf / inch was applied and the film was left in a 45°C oven for 24 hours. If the difference in water contact angle was △2° or more, the transfer was recorded as "Yes." If there was no difference in water contact angle, the transfer was recorded as "No."
[0161] The same transfer test was also carried out on the antistatic layer of the polyester release film, and the presence or absence of transfer was noted.
[0162] 3.Water contact angle The water contact angle of the release layer of the film was measured using a contact angle meter (KRUSS, DSA 100). 3 μl of pure water (S1, Volume mode) was dropped onto the film specimen, and the average water contact angle was measured for 15 seconds. A total of five measurements were taken, and the average values are shown.
[0163] 4. Diiodomethane contact angle The contact angle of diiodomethane on the release layer of the film was measured using a contact angle meter (KRUSS, DSA 100). 1 μl of diiodomethane (S1, Volume mode) was dropped onto the film specimen, and the average contact angle of diiodomethane for 15 seconds was measured. A total of 5 measurements were taken, and the average values are shown.
[0164] 5. Surface Energy The surface energy of the release layer of the film was calculated from the measurement results of the water contact angle and diiodomethane contact angle using the Owens-Wendt method.
[0165] 6. Processing and coating properties A UV resin (MIRAMER M1130, Miwon Specialty Chemical Co.) was applied to a thickness of 10 μm on the release layer of the film and cured by UV to prepare a sample. The processability and coating properties of the sample were evaluated according to the following criteria.
[0166] *1 grade - unit area (m2 )No pinholes *2nd grade - unit area (m 2 ) 2 pinholes or less per *3 grades - unit area (m 2 ) 5 or fewer pinholes per *4 grades - unit area (m 2 ) 10 or fewer pinholes per *5 grades - unit area (m 2 ) More than 10 pinholes per
[0167] 7. Peeling force A step of preparing a first sample by attaching an acrylate adhesive tape (NITTO #31B, manufactured by Nitto Denko, tape width: 25 mm) on the release layer of the polyester release film; a step of preparing a second sample by cutting the first sample into a size of 5 mm x 180 mm; and a step of applying 70 g / cm 2 and then peeling the tape 180° at a peeling speed of 300 mm / min using a peel tester.
[0168] 8. Friction-induced electrification potential The frictional static electricity for the polyester release film was measured using a rotary static tester (Daiei Kagaku Seiki MFG, RST-300a). At this time, the A side (the release layer side of the polyester release film) and the B side (the antistatic layer side of the release film) were rubbed at a rotation speed of 300 rpm for 180 seconds, and the amount of static electricity generated was measured.
[0169] 9.Surface resistance The surface resistance of the antistatic layer of the films prepared in the examples and comparative examples was evaluated. The measurement method was to measure the surface resistance using Mitsubishi Chemical Corp. Hiresta-Up MCP-HP450 equipment under the conditions of 25°C, 50% RH, 10V, and 10 seconds.
[0170] [Table 1]
[0171] Referring to Table 1 above, it was confirmed that the polyester release films according to the examples not only have excellent transfer properties, peelability, and coating processability compared to the release films according to the comparative examples, but also have excellent antistatic properties and a remarkably low frictional electrification voltage of less than 50 V.
[0172] Therefore, the polyester release film of the present invention includes a release layer including an aqueous coating composition including a polyester resin, an acrylic resin, and a polyolefin wax, and an antistatic layer including a water-dispersible antistatic composition including a conductive polymer, and thus not only has excellent peelability and coating processability, but also has excellent antistatic properties and a significantly low frictional charging voltage of less than 50 V, which prevents the generation of static electricity during film running and winding, and significantly reduces the amount of air or foreign matter that is introduced due to static electricity.
[0173] In addition, the polyester release film of the present invention can solve problems such as a decrease in yield due to unreacted materials and adhesion of foreign matter due to static electricity that occur when a coating layer is formed using the release film, and is suitable for use as a substrate when manufacturing optical films such as thin film polarizing plates.
Claims
1. The present invention includes a polyester base film, a release layer formed on one side of the base film, and an antistatic layer formed on the other side of the base film, the release layer comprises a water-based coating composition including a polyester resin, an acrylic resin, and a polyolefin wax; The polyester release film, wherein the antistatic layer comprises a water-dispersible antistatic composition that includes a conductive polymer.
2. 2. The polyester release film according to claim 1, wherein the polyester release film has a frictional charging voltage of less than 50V.
3. 2. The polyester release film according to claim 1, wherein the weight ratio of the solid content of the polyester resin to the solid content of the acrylic resin is 1:0.1 to 1:1.
5.
4. 2. The polyester release film according to claim 1, wherein the release layer comprises 20 to 50 parts by weight of polyolefin wax per 100 parts by weight of polyester resin.
5. 2. The polyester release film according to claim 1, wherein the polyolefin wax is one or more waxes selected from the group consisting of polyethylene waxes and polypropylene waxes.
6. The polyester release film according to claim 1 , wherein the conductive polymer comprises at least one selected from the group consisting of polythiophenes, polypyrroles, and polyanilines.
7. 10. The polyester release film of claim 1, wherein the water-dispersible antistatic composition further comprises a water-based polyurethane resin.
8. 8. The polyester release film according to claim 7, wherein the solid content of the water-dispersible antistatic composition comprises 1 to 30 wt % of a conductive polymer and 70 to 99 wt % of a water-based polyurethane resin.
9. The surface resistance of the antistatic layer is 10 10 2. The polyester release film according to claim 1, wherein the elastic modulus is Ω / □ or less.
10. 3. The polyester release film according to claim 1, having a haze of 90% or less and a processing coatability that satisfies the following formula 1: [Formula 1] N H =0 In the above formula 1, N H is the area per unit area (m2) when a UV resin is applied to a thickness of 10 μm on the release layer of the polyester release film and cured. 2 ) is the number of pinholes generated per
11. the release layer is formed by in-line coating of the aqueous coating composition, 2. The polyester release film according to claim 1, wherein the antistatic layer is formed by in-line coating of the water-dispersible antistatic composition.
12. 2. The polyester release film according to claim 1, wherein the base film is biaxially oriented, and the release layer and the antistatic layer are uniaxially oriented in the transverse direction (TD).
13. 2. The polyester release film according to claim 1, wherein the base film has a thickness of 10 to 300 μm, and the release layer and the antistatic layer have a thickness of 10 to 200 nm.
14. The polyester release film according to claim 1 , which is for protecting a polarizing plate.
15. A first step of preparing a polyester substrate film; A second step of applying a water-based coating composition containing a polyester resin, an acrylic resin, and a polyolefin wax to one side of the substrate film to form a release layer; A third step of applying a water-dispersible antistatic composition containing a conductive polymer to the other side of the substrate film to form an antistatic layer; and a fourth step of heat-treating, while stretching, a laminate comprising the base film, and a release layer and an antistatic layer formed on the base film.
16. The method for producing a polyester release film according to claim 15, wherein the fourth step comprises passing the laminate through a heat treatment device in which a total heat amount of air supplied to a passing section is 222,000 kcal / min to 229,000 kcal / min, thereby performing stretching and heat treatment.
17. The fourth step is a step of preheating the laminate by passing it through a section where a heat amount of 44,000 kcal / min to 46,000 kcal / min is supplied; Stretching the preheated laminate in a transverse direction (TD) while passing through a section to which a heat amount of 62,000 kcal / min to 64,000 kcal / min is supplied; and The method for producing a polyester release film according to claim 15, comprising the steps of: subjecting the stretched laminate to the heat treatment while passing through a section in which a heat amount of 114,000 kcal / min to 120,000 kcal / min is supplied.
Citation Information
Patent Citations
Polyester film for transfer foil
JP2006264135A
Protective layer transfer sheet and intermediate transfer medium
JP2014198433A
Polyester multilayer film
JP2019527152A
IoT-based automatic seed sprinkling system
KR1020230064238A
Double-sided pressure-sensitive adhesive sheet with release sheets
WO2011055689A1
